RHYTHMIC AND EXPRESSIVE ACTIVITIES IN AN INCLUSIVE PERSPECTIVE (Fiep Bulletin - online, 2011)
This article is based on an experience report established from the implementation of the extension project "Expressive and Rhythmic Activities for the Elderly", linked with the Residents Association of Jardim América, in Guarapuava/PR. This study has the pretension to establish a consistent dialogue between teory and practice, with regard to list the important elements that where observed during the performance of the activities. According to the local reality and culture, the need to adapt the choice of musics and choreography chances was observed. After these adjustments, the participants showed more interest requesting an extension of class time.
Keywords: Dance; Elderly; Extension Project